CLASTS OF UPPERMOST ALBIAN (VRACONIAN) LIMESTONE IN THE EOCENE CUCCURU 'E FLORES CONGLOMERATE OF THE M. ALBO MASSIF (EASTERN SARDINIA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
Rare clasts of richly fossiliferous uppermost Albian (Vraconian auctt.) glauconitic and phosphatic, ammonite-bearing limestone have been found in the Eocene Cuccuru ’e Flores Conglomerate in the area of M. Albo massif (eastern Sardinia). The limestone is wholly comparable in facies and fossil assemblage to the classical outcrop known in the Orosei area. The fossil content includes also brachiopods and abundant planktonic foraminifers of the Thalmanninella (formerly Rotalipora) appenninica Zone. In the palaeontological part the brachiopods Orbirhynchia parkinsoni and Capillithyris capillata are described and discussed. Vraconian highly condensed deposits, characterized by basal erosional gaps of variable importance, have particular relevance, being known to be widely distributed in the northern Tethyan margin with common characteristics, such as authigenic glauconite, phosphatic nodules and a rich outer-shelf fauna.
Keywords: Uppermost Albian clasts; Eocene conglomerate; Macrofossils; Brachiopods; Planktonic foraminifers; Palaeogeography; Eastern Sardinia